2017
DOI: 10.1016/j.ijpharm.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aggregate and silicone-oil counts in pre-filled siliconized syringes: An orthogonal study characterising the entire subvisible size range

Abstract: Characterisation of particulates in therapeutic monoclonal antibody (mAb) formulations is routinely extended to the sub-visible size-range (0.1-, with the increased use of prefilled syringes (PFS), particle differentiation is required between proteinaceous and non-proteinaceous particles such as silicone-oil droplets. Here, three orthogonal techniques: Raster Image Correlation Spectroscopy (RICS), Resonance Mass Measurements (RMM) and Micro-Flow Imaging (MFI), were evaluated with respect to their sub-visible p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…2,3 Here, we demonstrate that HVM can detect, differentiate and identify multiple distinct populations of subvisible particles when they are present simultaneously in complex heterogeneous dispersions, including the most common categories of subvisible contaminants that are introduced into biopharmaceutical products during the various stages of development, manufacturing and use. These include subvisible protein aggregates in combination with oil droplets, 4,5 degradants of surfactants, 6 metal particles 7 and air bubbles. 8 All such particle types are indistinguishable to conventional particle characterization technologies including microflow imaging (MFI) and HIAC.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Here, we demonstrate that HVM can detect, differentiate and identify multiple distinct populations of subvisible particles when they are present simultaneously in complex heterogeneous dispersions, including the most common categories of subvisible contaminants that are introduced into biopharmaceutical products during the various stages of development, manufacturing and use. These include subvisible protein aggregates in combination with oil droplets, 4,5 degradants of surfactants, 6 metal particles 7 and air bubbles. 8 All such particle types are indistinguishable to conventional particle characterization technologies including microflow imaging (MFI) and HIAC.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where fluorophore photobleaching is a concern, raster image correlation spectroscopy (RICS) is similar to FCS but applies multiphoton excitation and rasterized scanning to limit fluorophore exposure to light (Fig. 5) (Dong et al, 2010;Shah et al, 2017).…”
Section: Current Challenges and Opportunitiesmentioning
confidence: 99%
“…7,8 Pre-filled syringes are often coated with the silicone oil polydimethylsiloxysilane (PDMS) to lubricate the plunger and allow free movement, 9 especially important for dealing with high frictions arising from the highly viscous solutions under high mAb concentrations, 2,7 This oil film is typically a few µm thick and presents a large hydrophobic surface to which mAbs may adsorb or break loose and form suspended oil droplets in the mAb solution, particularly with shake-stress as may be encountered during packaging, transport and storage. 10 Vials coated with PDMS are also used to minimise proteinsurface interactions and reduce aggregate formation during lyophilisation (freeze-drying) of mAb products. 11 MAbs, like most proteins, are amphiphilic, and tend to adsorb to accessible surfaces and interfaces, a process which can potentially cause structural rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The exact mechanism for this destabilisation is not currently known but most hypotheses relate to the adsorption of mAbs to the oil surface. 12 Though there is not yet any direct structural evidence of mAb adsorption causing denaturation, it has been suggested that mAb adsorption promotes the formation of oil droplets under agitation providing nucleating sites for aggregation 10 and both droplet formation by emulsification and protein aggregate formation are heavily associated with mAb adsorptiondesorption processes at the silicone/water interface, the oil effectively catalysing protein structural damage. 14,15 Literature investigating the adsorbed structure of mAbs adsorbed at fluid/fluid interfaces is relatively sparse, despite the importance of this topic.…”
Section: Introductionmentioning
confidence: 99%